Chain-length effect on binary superlattices of polymer-tethered nanoparticles. (20th May 2020) - Wang, Ke; Li, Fan; Jin, Seon-Mi; Wang, Kui; Tian, Di; Hussain, Mubashir; Xu, Jiangping; Zhang, Lianbin; Liao, Yonggui; Lee, Eunji; Yi, Gi-Ra; Xie, Xiaolin; et al.
Abstract : The co-assembly behavior of polymer-tethered NPs is determined by the chain-length of the polymer ligand on the two sized NPs, and exhibits three different models, where each one has its own key factor that determines the crystalline structure. Abstract : Binary inorganic nanoparticles (NPs) can be assembled into various types of superlattices depending on the size ratio, shape, and interparticle potential, which may tailor the mechanical, optical and electronic properties. Here, polymer-stabilized gold NPs are assembled into binary nanoparticle superlattices (BNSLs) and their structures were precisely controlled by tuning the size ratio of NPs as well as the chain length of polymer ligands. Typically, binary gold NPs with short-chain polymer ligands showed the phase behaviors of hard-sphere colloids. By contrast, ones with long-chain polymer ligands showed the phase behavior of soft-sphere binary colloids. Interestingly, mixed binary NPs with short-chain and long-chain polymer ligands showed unnatural binary NP superlattices in thin films, in which small NPs are contained in octahedral voids of the regular HCP lattice. Our finding can be further extended to other types of functional NPs, which may tune various properties for devices.